Relationship between Self-directed Learning and Problem-solving with the Mediate Role of Academic Self-efficacy and Moderating Gender in Students - Imran, Ansaf Jasim; Sajjadian, Ilnaz; Al-Mamouri , Ali Hussein Mazloum; Nadi, Mohammad Ali (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to investigate the relationship between self-directed learning and problem-solving skills among university students, considering the mediating role of academic self-efficacy and the moderating effect of gender.Methods and Materials: The research employed a descriptive-correlational design and structural equation modeling (SEM). The study population included all students at Al-Qadisiyah University in Iraq during the 2023–2024 academic year. A sample of 300 students was selected through convenience sampling. Data were collected using three standardized instruments: the Problem-Solving Styles Questionnaire (Cassidy & Long, 1996), the Self-Directed Learning Questionnaire (Cheng et al., 2010), and the Academic Self-Efficacy Questionnaire (Owen & Froman, 1988). Pearson correlation coefficients and SEM with SmartPLS software were applied for statistical analysis. Reliability and validity indices confirmed the appropriateness of the instruments and measurement models.Findings: Results demonstrated significant positive correlations between self-directed learning, academic self-efficacy, and problem-solving skills. Path analysis indicated that self-directed learning directly influenced problem-solving (β = 0.213, p < 0.01) and academic self-efficacy (β = 0.515, p < 0.01). Academic self-efficacy, in turn, significantly predicted problem-solving ability (β = 0.488, p < 0.01). Furthermore, academic self-efficacy partially mediated the relationship between self-directed learning and problem-solving (indirect effect β = 0.252, p < 0.01). Gender also moderated the relationship, as indicated by significant differences in problem-solving performance between male and female students (β = 0.132, p < 0.01). The model showed satisfactory fit indices, with R² values indicating that 26.26% of the variance in academic self-efficacy and 37.5% of the variance in problem-solving were explained by the predictors.Conclusion: The findings highlight that enhancing students’ self-directed learning abilities strengthens academic self-efficacy, which in turn improves problem-solving skills. Gender differences further shape these relationships, underscoring the need for tailored educational strategies.